A FORECASTING ANALYSIS OF CAR WHEEL RIM DEMAND AT PT. XX TO REDUCE WASTE USING POM-QM SOFTWARE - Paramitha, Aditya; Saifuddin Z.S, Joumil Aidil (Barometer, 2023)
PT. XX is one of the car wheel rim companies in Indonesia whose products are sent to a number of local and international assembly companies. The main goal of this research is to forecast the demand for car wheel rim production using three forecasting methods at PT. XX. The research results are in the form of the value of demand forecasting calculation along with the error rate. It is known that there are three methods used, namely Single Moving Average, Weighted Moving Average, and Single Exponential Smoothing methods. Based on calculations from the POM-QM software, the method that is suitable to be applied in this research is the Weighted Moving Average method because the smallest error value is obtained as in the MAPE error value is 12.124%, the Mean error value is 1177.773 the MAD error value is 24587.23, the MSE error value is 1099377000, and the forecast value in the next period is 243013 units. Through this research and forecasting, the writer hoped that PT. XX could consider it a plan for the next batch of production.